2011
DOI: 10.5944/educxx1.14.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Familia Y Escuela Ante La Incorporación De Las Tecnologías De La Información Y La Comunicación

Abstract: RESUMENEl objetivo de esta investigación ha sido conocer la valoración que hace la familia del alumnado (autóctono y extranjero) de Educación Infantil y Primaria de la Comunidad Autónoma de la Región de Murcia, sobre el uso y la interacción comunicativa con las TIC. En la metodología se utiliza un diseño transversal en consonancia con la finalidad investigadora, para recoger la opinión de la muestra seleccionada de 1932 familias, mediante la aplicación del cuestionario como instrumento de recogida de informaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 2 publications
0
3
0
15
Order By: Relevance
“…In turn it should be noted that "parents without studies" are those who consider less important (12.2%) such incorporation into the current educational system. In contrast to university students who only 1.8% do not consider it (Ballesta & Cerezo, 2011). In counterpart, the results of the research showed that 6.49% said they strongly disagree with the use of ICTs in youths, while 35% said that they are neutral among the nor-acceptance or acceptance of the use and 27.7% say they agree.…”
Section: Discussionmentioning
confidence: 65%
“…In turn it should be noted that "parents without studies" are those who consider less important (12.2%) such incorporation into the current educational system. In contrast to university students who only 1.8% do not consider it (Ballesta & Cerezo, 2011). In counterpart, the results of the research showed that 6.49% said they strongly disagree with the use of ICTs in youths, while 35% said that they are neutral among the nor-acceptance or acceptance of the use and 27.7% say they agree.…”
Section: Discussionmentioning
confidence: 65%
“…Another aspect that directly affected the use of ICT in collaborative work was the socioeconomic status of the participants -Sig.≤0.007-: individuals with lower socioeconomic levels demonstrated greater use of technology for the purposes that are outlined in this paper. However, considering the digital breach in society at present, which is understood as yet another declaration of social inequality (Ballesta & Cerezo, 2012;Bautista, 2010), the study results allow us to observe how the opportunities that are offered at present by the ICT favour or enrich the interpersonal contexts of learning and collaboration between health sector partners in Colombia (Kollöffel, Eysink, & Jong, 2011;Gómez, Puigvert, & Flecha, 2011;Salmerón, Rodríguez, & Gutiérrez, 2010) and, in this work, they concentrate on low socioeconomic workers.…”
Section: Resultsmentioning
confidence: 99%
“…En general, estos estudios se centran en el contexto del hogar y de la familia, sin establecer vínculos con los procesos de transformación tecnológica que, dirigidos desde política educativa, se fomentan desde las aulas hacia la sociedad a través de iniciativas como la de la Escuela 2.0. Los pocos estudios que han reflexionado sobre el rol de la tecnología con una mirada holística se han centrado en la comunicación familia-escuela (Ballesta & Cerezo, 2011), sin analizar el impacto de los usos tecnológicos en el aprendizaje informal o en las dinámicas familiares. En este sentido, Ballesta & Cerezo (2011: 153) constatan la necesidad de "llegar a comprender y valorar el papel que tiene la familia en el uso de las TIC y su importancia dentro del ámbito escolar, ya que las familias pueden condicionar el uso de estos medios a favor de los alumnos".…”
Section: El Rol Clave De La Familia Dando Soporte a La Educación Digitalunclassified